Acidic profile in two different muscles of Nero Siciliano pigs as affected by different finishing diets - Di Rosa A.; Chiofalo V.; Lo Presti V.; Scianò S.; Zumbo A. (7th International Symposium on the Mediterranean Pig, 2012)
Fat and fatty acids contribute significantly and in various ways to meat quality and are central to the nutritional value of meat. Meat quality is also influenced by intrinsic factors such as muscle type. Therefore, the study examined the fatty acid composition of the white (Longissimus dorsi - LD) and the red (Psoas major - PM) muscle from 24 Nero Siciliano pigs fed with two different diets. The trial was carried out in the Nebrodi mountain area of Sicily (Italy). During the fattening period, the animals were divided into two groups, kept in two distinct wooded areas of 6 hectares each, and fed exclusively on acorn (A) and germinated barley (B). Results showed a strong interaction between diet and muscle type. The PUFA to SFA ratio was higher in PM muscle for both diets with A 0.16 LD vs 0.25 PM (P≤0.0001) and B 0.16 LD vs 0.21 PM (P≤0.001). The C18:2 n-6 amount, entirely derived from the diet, showed high statistical significance both as dietary effect and as intrinsic (muscle-type related) factor. In order to further improve strategies for pork production, more information on the effects of inherent factors (e.g. muscle type) on meat traits is needed.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)